Simulação computacional de evacuação em edificação de reunião de público: o estudo de caso do Centro de Convenções da Universidade Federal de Santa Maria - Uliana, Renan Somavilla (2022)
With the technological advancement in the area of fire safety (SCI), computational evacuation simulation tools emerge to assist architects and engineers in decisionmaking, in the face of different situations and design solutions, in the analysis of the weaknesses and strengths of buildings, and in readjustments and improvements to the built environment. This study aimed to analyze, through computer simulation scenarios, considering the evacuation in normal situation and in a panic situation, the evacuation time of the building, the flow rate and the specific flow of the access doors and emergency exits, the dynamics of movement of the occupants and the identification of critical points related to the evacuation process of the Convention Center of the Federal University of Santa Maria/RS. The building modeling was developed with the aid of the Pathfinder program, which allowed the simulation by the SFPE mode (Society of Fire Protection Engineers), based on numerical modeling techniques, based on the output flow and the Steering mode, with the combination of mechanisms steering and collision handling. Through simulations, in scenarios with occupants in normal evacuation conditions, the longest evacuation time was 485 seconds, the doors that most contributed to the exit of the building were PA 03 and PA 06, the highest flow rate was in port PA 03, with the passage of 2.21 occupants/second, as well as the highest specific flow, with the passage of 1.30 occupants/m.s. For scenarios with occupants in a panic condition during evacuation, the longest abandonment time was 217 seconds, the doors that proved to be the most effective for escaping the building were PSE 03, PSE 05 and PSE 06, the highest flow rate of registered was at the PSE 06 door, with the passage of 3.87 occupants/second, as well as the highest specific flow, with the passage of 2.15 occupants/m.s. The critical points identified in the study of the building are the circulations/stairways for accessing and exiting the rows of seats, as a possible place of congestion, and a pillar in the foyer, as a possible obstacle, both at the mezzanine level. The movement of the occupants in the evacuation scenarios of the SFPE mode was configured in queues, and in the Steering mode, the movement was spontaneous and random. In view of the study, it is expected to contribute to the academic and professional circles, promoting the use of computational simulation tools as an auxiliary instrument for the analysis and elaboration of projects in the area of fire safety in buildings.